2011
DOI: 10.4197/med.18-2.5
|View full text |Cite
|
Sign up to set email alerts
|

Foot Care Knowledge and Practice among Diabetic Patients Attending Primary Health Care Centers in Jeddah City

Abstract: Diabetics' knowledge and awareness on foot care are usually associated with less foot complications and better diabetic foot condition. A cross-sectional study to assess patients' foot care knowledge and practice was designed. A questionnaire to assess foot care knowledge and practices, and other related variables was conveyed through interviewing 747 diabetic patients in 7 representative primary health care centers in Jeddah city. A lower level of foot care knowledge than the optimum was noticed, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 19 publications
6
24
0
Order By: Relevance
“…Many other studies showed the presence of inadequate knowledge of self-foot-care in diabetic patients [18,19]. In Saudi Arabia, a group of studies highlighted a lower level of foot care knowledge than the optimum [13,20]. All researchers indicated the need for foot care education programs and improving the way of delivering it.…”
Section: Discussionmentioning
confidence: 99%
“…Many other studies showed the presence of inadequate knowledge of self-foot-care in diabetic patients [18,19]. In Saudi Arabia, a group of studies highlighted a lower level of foot care knowledge than the optimum [13,20]. All researchers indicated the need for foot care education programs and improving the way of delivering it.…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers expressed the need for foot care education programs and improve the way of delivering it. Some inadequacies of foot care practice in our subjects include also non-inspection of the inside of their footwear and wearing shoes without socks 12,14 . The contrast between the studies is maybe due to differences in comprehensive prevention programs which include proper screening, education, and concentration on high-risk feet between UKMMC and other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the practice score was significantly lower in patients with lower educational level. In addition, there is a significant relationship between the low level of knowledge on foot care and the reduction in exercise practices among the elderly 14 . Out of concern, older adults either man or women are more prone to foot ulcers with diabetes duration than the history of diabetes over 16 years compared with those with less than 15 years 7,11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations